Allometry and condition index in the freshwater bivalve Parreysia favidens (Benson, 1862) from river Bhadra, India - Thippeswamy, Seetharamaiah; Malathi, Shettigar; Anupama, N. M. (Indian Journal of Fisheries, 2014)
The morphometry, length-weight relationship and condition index of the freshwater bivalve Parreysia favidens (Benson, 1862) inhabiting the river Bhadra in the Western Ghats were examined from October 2001 to December 2002. The linear regression equations of length-breadth and length-width for the entire study period were L = 0.2653 + 0.5992 B and L = 0.2176 + 0.4403 W respectively. The monthly b values of length-breadth and length-width relationships varied from 0.5371 (November 2002) to 0.6915 (July 2002) and from 0.4132 (October 2002) to 0.5242 (July 2002) respectively. The data on length-total weight (W= 0.2418 L2.785), length- wet tissue weight (W=0.04859 L2.599) and length-dry weight (W=0.01177 L2.499) showed non-linear patterns. The coefficient of allometry, b ranged from 2.2485 (November 2002) to 3.4107 (July 2002) for length-total weight relationship and from 2.2779 (December 2002) to 2.8346 (January 2002) for length-wet tissue weight relationship. The values for length-dry tissue weight relationship fluctuated between 2.1528 (December 2002) and 2.9736 (January 2002). The monthly mean values of the condition index varied from 4.57 (October 2001) to 8.95 (April 2002). The variation in condition index followed the breeding period and seasons. The data indicated that the condition of mussels was fairly good from April to October. The best time for commercial exploitation appears to be during April to October when the mussels are in good condition.